LITERATURE RIVIEW : Hubungan Aktivitas fisik lansia dengan resikonya terjadinya osteoarthritis knee - Pandu Febriyanto (2022)
In the elderly, the movement and function of the body experience a progressive decline, so that it can interfere with daily activities. This reduction will increase the level of laziness in doing activities and exercises that will cause pain later on, including the knee. The knee has a supportive function to the body, it also has a walking function. The knee will have severe pain and inflammation if it is not moved too long or if it rarely does any activity. Inflammation of the knee or commonly known as osteoarthritis of the knee The knee is a degenerative illness that occurs due to the thinning of the cartilage in the knee. So one of the things you can do with an elderly person is physical activity. The objective of this study was to determine and analyse the link between physical activity in the elderly and the risk of osteoarthritis of the knee. The search method used is a literature review, looking for documentary sources using several keywords that were pre-sorted during the 2016-2021 period. The results of the literature review indicated that four articles and journals met the inclusion criteria and were suitable for the topic. After analysis of 4 journals, the results showed that there was an association between physical activity and the risk of osteoarthritis of the knee. The conclusion is that physical activity is associated with the risk of osteoarthritis of the knee.